Possibilities and limitations of micellar electrokinetic chromatography separation of very hydrophobic anthraquinone dyes using SDS micelles - Česla, Petr; Fischer, Jan; Miková, Markéta; Jurčáková, Petra (University of Pardubice, 2009)
The separation of five very hydrophobic anthraquinone dyes and five polar anthraquinone dye intermediates by micellar electrokinetic chromatography has been studied. Both types of analytes were separated using non-coated fused silica capillary in borate background electrolyte containing sodium dodecyl sulphate micellar pseudostationary phase. Acetonitrile was used for modification of polarity of the background electrolyte. The migration of anthraquinones was characterized by lipophilic and polar indices employing n-alkylbenzenes as calibration standards. Based on the achieved results, the types of the interactions of anthraquinones with sodium dodecyl sulphate micelles and acetonitrile in aqueous phase are described. The limits of micellar electrokinetic chromatography for successful separation of very hydrophobic compounds are discussed.